واقع إدارة الأزمات بالمكتبات الجامعية... دراسة (Comprehensive Journal of Science, 2025)
This study aims to examine the impact of the library environment, infrastructure, administrative, and technical factors on crisis management in an academic library. The descriptive-analytical method was employed, and a structured questionnaire was distributed to a sample of 38 respondents. After excluding invalid responses, the final sample consisted of 34 valid questionnaires, representing a response rate of 89.5%, which is considered acceptable in social and human sciences research. The reliability test yielded a Cronbach’s Alpha of 0.729, indicating a good level of reliability and internal consistency of the instrument.The findings revealed a statistically significant positive relationship between the library environment and crisis management (r = 0.346, Sig. = 0.023), suggesting that improving the internal environment enhances the library’s capacity to manage crises. In contrast, library infrastructure showed a weak and statistically insignificant relationship (r = 0.281, Sig. = 0.107), reflecting its limited influence on crisis management. Moreover, a strong and statistically significant relationship was found between administrative factors and crisis management (r = 0.574, Sig. = 0.000), as well as between technical factors and crisis management (r = 0.551, Sig. = 0.001). This highlights the crucial role of administrative practices and modern technologies in strengthening the library’s ability to effectively respond to crises.Based on these results, the study recommends improving the library environment in terms of lighting, ventilation, and sufficient space allocation; upgrading the infrastructure and service facilities; adopting comprehensive planning tools for potential crises; and enhancing the use of modern technologies in archiving, protecting, and securing information resources.Overall, the study provides both theoretical and practical insights that can guide academic libraries in developing strategies and policies to ensure service continuity and sustainability during crises.